Kepuasan Pasien Terhadap Pelayanan Keperawatan (Caring) Di Ruang Rawat Inap - Yulandasari, Vera; Sutomo, Suswinda Yuli; Suhamdani, Haris; Mastuty, Amalia (Jurnal Kesehatan Qamarul Huda, 2020)
Nurse behavior is one indicator that determines the level of patient satisfaction. The nurse's behavior which is classified as bad often causes the patient to feel dissatisfied. To determine the effect of nurses' behavior in serving patients on patient satisfaction in the Flamboyan inpatient room at Praya Hospital. The research design used in this study was correlational with a cross sectional approach. The sample in this study were 41 patient respondents who were selected by the incidental sampling technique. The research data were collected using a questionnaire. This study showed that most of the patient respondents stated that they were not satisfied, namely as much as 58.5%. Based on the results of the chi square statistical test, it was found that there was a relationship with the level of satisfaction p = 0.005. Good nurse behavior in the form of caring can provide satisfaction to patients during treatment.